A Review of Post-Processing Technologies in Additive Manufacturing - Peng, Xing; Kong, Lingbao; Fuh, Jerry Ying Hsi; Wang, Hao (Journal of Manufacturing and Materials Processing, 2021)
Additive manufacturing (AM) technology has rapidly evolved with research advances related to AM processes, materials, and designs. The advantages of AM over conventional techniques include an augmented capability to produce parts with complex geometries, operational flexibility, and reduced production time. However, AM processes also face critical issues, such as poor surface quality and inadequate mechanical properties. Therefore, several post-processing technologies are applied to improve the surface quality of the additively manufactured parts. This work aims to document post-processing technologies and their applications concerning different AM processes. Various types of post-process treatments are reviewed and their integrations with AM process are discussed.